Comparison Of Cost, Surface Roughness And Time Using Stereo Litography And 3d Printer For The Design Of Composite Pedal - Lee, Ho Boon (2003)
This research presents the process of designing a non metal pedal box system for Proton Wira car. Closed form or non-numerical data analysis of non metal pedal box system is initially carried out. Calculations of bending stiffness and torsion strength to decide on the best pedal lever cross section were carried out. Similarly yield stress calculation for pedal lever was performed. Comparison between non metal pedal box system and steel pedal box system was carried out. This research also includes the measuring process with a coordinate measuring machine of the currently used steel pedal box system and followed by modelling the design in Unigraphics. The design of three pedals namely an accelerator pedal, a brake pedal and a clutch pedal as well as a mounting bracket was carried out. Rapid prototyping models using stereo lithography (SLA 3500) by 3D System and 3D Printer Z40L. by Z-corp were produced. Stereolithography and 3D printing were compared in terms of cost, speed of the process, user friendliness and model quality. The purpose of rapid prototyping models is to facilitate easy communication of product to the customers.methods of rapid prototyping using various approaches and to decide on the best methods in term of quality, cost and speed of processing. Design communication using rapid prototyping is one of the important elements of concurrent engineering technique. The pedal box' system was designed to meet the final objective of weight reduction produced using injection moulding process.